Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Die Sporthalle – Ein Raum zum Sprachenlernen? Zwischen der Forderung nach Integration durch Sport und Sprache(n) als Schlüssel zur Integration - Treder, Alexandra (Transdisziplinäre Räume in den Kulturwissenschaften)

Sprachbezogene Kompetenzerwartungen im Sportunterricht – Eine systematische Lehrplananalyse - Grimminger-Seidensticker, Elke; Treder, Alexandra; Niederhaus, Constanze (Zeitschrift für Sportpädagogische Forschung)

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. Print-ISBN 978-3-8309-4711-0. E-Book-ISBN 978-3- 8309-9711-5. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Diskriminierung begegnen – Vielfalt gestalten : Veranstaltungsreihe von und für Studierende und Interessierte - Treder, Alexandra

Mit Methoden der Drama- und Erzählpädagogik Fremdsprachen lernen - Meyberg, Sora; Treder, Alexandra